This is a Man’s world : autorité et pouvoir genrés dans le milieu des banques centrales - Guillaume Vallet (Revue de la Régulation)
This article deals with the issue of gender in central banks. The latter are characterized by male domination, since there are still few women as chairpersons or exerting a high-ranked status within central banks. Resting on qualitative methods involving both six interviews conducted with female governors or women close to the top-level functions within central banks, and the analysis of central banks official data, we hypothesize that there is a mismatch between power and authority, which is unfavorable to women. Even though our results only partially confirm our hypothesis, we stress the need to change attitudes and hiring procedures in central banks, in order to promote new roles for women in this field. This change is likely to improve both the whole functioning and the governance of central banks.